2021
DOI: 10.1111/gcb.15603
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying high‐temperature stress on soybean canopy photosynthesis: The unique role of sun‐induced chlorophyll fluorescence

Abstract: High temperature and accompanying high vapor pressure deficit often stress plants without causing distinctive changes in plant canopy structure and consequential spectral signatures. Sun‐induced chlorophyll fluorescence (SIF), because of its mechanistic link with photosynthesis, may better detect such stress than remote sensing techniques relying on spectral reflectance signatures of canopy structural changes. However, our understanding about physiological mechanisms of SIF and its unique potential for physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 77 publications
0
25
0
Order By: Relevance
“…A tower-based canopy SIF system called FAME, developed very recently by Gu et al [27], significantly improved both the hardware and software designs, and their measurements showed that canopy-leaving directional SIF emissions saturated or even decreased at high light. In a recent high-temperature experiment, Kimm et al [30] found that both light use efficiency and SIF yield decreased with increasing heat stress when PAR was not a limiting factor. These two studies highlighted the role of the dark reactions in the partitioning of absorbed solar radiation to the different pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A tower-based canopy SIF system called FAME, developed very recently by Gu et al [27], significantly improved both the hardware and software designs, and their measurements showed that canopy-leaving directional SIF emissions saturated or even decreased at high light. In a recent high-temperature experiment, Kimm et al [30] found that both light use efficiency and SIF yield decreased with increasing heat stress when PAR was not a limiting factor. These two studies highlighted the role of the dark reactions in the partitioning of absorbed solar radiation to the different pathways.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy may be partially due to the designs of SIF-observing systems and protocols for measurements [29]. Compared with SIF variability driven by incident light, the magnitude of changes in SIF in response to changes in the dark reactions is so subtle that it may be unobservable or uninterpretable for some measuring systems [30]. In order to quantify possible changes in ChlF due to changes in the dark reactions, all of the involved processes in both the light and dark reactions of photosynthesis should be carefully observed.…”
Section: Introductionmentioning
confidence: 99%
“…Within the range of plant growth, an increase in temperature will lead to an increase in photosynthesis [48]. However, stresses induced by particularly higher temperatures decrease SIF values through the decrease in red and far-red fluorescence [24,25]. Ren et al [49] has also argued that in subtropical vegetation, the end of the growing season was positively correlated with the pre-season minimum temperature.…”
Section: Effect Of Temperature and Precipitation On Plant Photosynthesismentioning
confidence: 99%
“…SIF also offers advantages in the study of vegetation phenology because it is sensitive to both the initial and final stages of photosynthesis, which are not mechanistically linked to leaf greenness [6,23]. SIF may better detect water stress and temperature stress in vegetation than VIs, which rely on the spectral reflectance signatures produced by changes in canopy structure [24]. In tropical rainforests, SIF decreases in the dry season, resulting in a decrease in GPP, which indicates that SIF varies with water availability and that drought weakens the ability of vegetation to engage in carbon fixation [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation